A new species of Gypsophila (Caryophylloideae, Caryophyllaceae) from Iran - Nejad Falatoury, Atiye; Assadi, Mostafa; Ghahremaninejad, Farrokh (Phytotaxa, 2015)
As a result of the recent revision of the genus Gypsophila of Iran, a new species, Gypsophila alvandica sp. nov. (sect. Dichoglottis) is here described and compared with the related G. polyclada. These two species differs by number of stems, type of indumentum, shape and color of the petals and size and coat of the seeds. G. alvandica is endemic to the central-western of Iran.